2013
DOI: 10.1080/00223891.2013.866569
|View full text |Cite
|
Sign up to set email alerts
|

The MMPI–2 Restructured Form Personality Psychopathology Five Scales: BridgingDSM–5Section 2 Personality Disorders andDSM–5Section 3 Personality Trait Dimensions

Abstract: This study examined in a college sample and a sample of non-treatment-seeking, trauma-exposed veterans the association between the MMPI-2 Restructured Form (MMPI-2-RF) Personality Psychopathology Five (PSY-5) Scales and DSM-5 Section 2 personality disorder (PD) criteria, the same system used in DSM-IV-TR, and the proposed broad personality trait dimensions contained in Section 3 of DSM-5. DSM-5 Section 2 PD symptoms were assessed using the SCID-II-PQ, and applying a replicated rational selection procedure to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
32
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 28 publications
9
32
1
Order By: Relevance
“…Sellbom, Smid, De Saeger, Smit, and Kamphuis (2014) demonstrated that the MMPI-2-RF PSY-5 scales were significantly and meaningfully associated with PD criteria assessed through structured clinical interviews in Dutch clinical and forensic samples; many of these findings were replicated in Finn et al (2014). Similarly, added that the full set of MMPI-2-RF scales predicted DSM-5 Section II PD criteria for 7 of the 10 PDs (with sufficient variability) in those same samples.…”
Section: Assessing Personality Pathology With the Mmpimentioning
confidence: 65%
See 2 more Smart Citations
“…Sellbom, Smid, De Saeger, Smit, and Kamphuis (2014) demonstrated that the MMPI-2-RF PSY-5 scales were significantly and meaningfully associated with PD criteria assessed through structured clinical interviews in Dutch clinical and forensic samples; many of these findings were replicated in Finn et al (2014). Similarly, added that the full set of MMPI-2-RF scales predicted DSM-5 Section II PD criteria for 7 of the 10 PDs (with sufficient variability) in those same samples.…”
Section: Assessing Personality Pathology With the Mmpimentioning
confidence: 65%
“…For example, the item pool could be decomposed into commonly recognized major dimensions of internalizing, externalizing, and thought disorder dimensions-consistent with current conceptions within quantitative psychopathology (e.g., Caspi et al, 2014;Kotov et al, 2011;Markon, 2010;Wright et al, 2013) and the Hierarchical Taxonomy of Psychopathology (HiTOP; Kotov et al, 2017). This property, along with the established cross-connections between categorical and dimensional PD constructs, indicates that the MMPI-2-RF might support the development of PD spectra based on traditional DSM diagnoses (see also Finn et al, 2014).…”
Section: Assessing Personality Pathology With the Mmpimentioning
confidence: 99%
See 1 more Smart Citation
“…To assess personality, on the other hand, several instruments have been proposed, such as, The Big Five Inventory (BFI) and Personality Inventory Revised -NEO PI-R (Miller et al, 2011), Multidimensional Personality Questionnaire -MPQ , Schedule for Non-adaptive and Adaptive Personality (SNAP) and Minnesota Multiphasic Personality Inventory -MMPI (Finn et al, 2014), for instance.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the five higher order factors of the FFM have been regarded as a valid dimensional system that may potentially represent the major dimensions that constitute personality (Costa & Widiger, 2002) and hold similarity with the five pathological personality trait domains suggested in the DSM-5 (negative affectivity vs. emotional stability, detachment vs. extraversion, antagonism vs. agreeableness, disinhibition vs. conscientiousness, psychoticism vs. lucidity). In addition, the five domains of pathological personality traits as presented in the DSM-5 share conceptual similarity with the Personality Psychopathology Five (PSY-5; Harkness, 1992;Harkness, Reynolds, & Lilienfeld, 2014), namely aggressiveness, disconstraint, negative emotionality/neuroticism, and introversion/low positive emotionality in studies examining its concurrent validity (Finn et al, 2014;Harkness et al, 2014). The traits composing the PSY-5 have been hypothesized to reflect the five major human adjustment systems, namely reality modeling for action, short-term danger detection, long-term cost-benefit projection, resource acquisition, and agenda protection (Harkness et al, 2014).…”
mentioning
confidence: 99%